A Project Based-Learning Design in 2D and 3D CADD Training with Inventor 2020 for Increasing Teachers’ Competence of Machinery Engineering - Rahman, Rifki Zainur; Widiyanti, Widiyanti; Nurhadi, Didik (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Teachers with good competency will impact the quality of Education. The teachers' responsibility in educating, teaching, guiding, managing, training, and evaluating must be well-developed so that the results can directly contribute in improving the quality of education because qualified teachers could manifest a highly qualified education. Therefore, some factors that have determinant values need to be considered as necessary to construct qualified teachers. Teachers' competency improvement can be made in various ways, including through the training session. Teacher training aimed to advance the competence of teachers, especially for Machinery Engineering teachers so that they can meet the specified standards. The training model designed in the paper sought to explain 2D and 3D CADD training with the 2020 inventor using the project-based learning model. This paper was expected to be able to manifest the concept of teacher training using Project Based-Learning in training institution so that it can be able to help in improving the teachers' competency